الصحة النفسية لدى التلاميذ المعاقين سمعيا - دايخة، أسماء, بالعشي، صفاء (جامعة الوادي university of Eloued, 2020)
ملخص الدراسة تهدف الدراسة الحالية للتعرف على مستوى الصحة النفسية لدى المعاقين سمعيا، حيث أجريت الدراسة على عينة قوامها "30" تلميذ وتلميذة، وتم الاعتماد على المنهج الوصفي الاستكشافي، وذلك باستخدام مقياس الصحة النفسية للتحقق صحة الفرضيات التالية: - نتوقع أن مستوى الصحة النفسية لدى المعاقين سمعيا مرتفع. - نتوقع أن الصحة النفسية لدى المعاقين سمعيا مرتفعة عند الذكور أكثر من الإناث. - نتوقع أن الصحة النفسية لدى المعاقين سمعيا ترجع للعمر لصالح (18-13). - نتوقع أن الصحة النفسية لدى المعاقين سمعيا ترجع لنوع الإعاقة لصالح الصم. - نتوقع أن الصحة النفسية لدى المعاقين سمعيا ترجع للمستوى الاقتصادي لصالح (متوسط). وخلصت الدراسة إلى ما يلي: - مستوى الصحة نفسية لدى المعاقين سمعيا مرتفع. - توجد فروق ذات دلالة إحصائية في مستوى الصحة النفسية لدى المعاقين سمعياً ترجع للجنس لصالح الذكور. - توجد فروق ذات دلالة إحصائية في مستوى الصحة النفسية لدى المعاقين سمعيا ترجع للعمر لصالح (18-13). - توجد فروق ذات دلالة إحصائية في مستوى الصحة النفسية لدى المعاقين سمعيا ترجع لنوع الإعاقة لصالح الصم. - توجد فروق ذات دلالة إحصائية في مستوى الصحة النفسية لدى المعاقين سمعيا ترجع للمستوى الاقتصادي لصالح (متوسط).   Abstract The purpose of this study is to identify the level of mental health in the hearing impaired, as the study was conducted on a sample of "30" students, and the descriptive exploratory approach was used, using the mental health scale to check the following assumptions:  We expect the level of mental health of the hearing impaired to be high.  We expect the mental health of the hearing impaired to be higher for men than for women.  We expect that the mental health of the hearing impaired is due to age in favor of (18-13).  We expect that the mental health of the hearing impaired is due to the type of disability in favor of the deaf.  We predict that the mental health of the hearing impaired is due to the economic level in favor of (average). The study concluded that:  The level of mental health of the hearing impaired is high.  There are statistically significant differences in the level of mental health of the hearing impaired due to gender in favor of men.  There are statistically significant differences in the level of mental health of the hearing impaired due to age in favor of (18-13).  There are statistically significant differences in the level of mental health of the hearing impaired due to the type of disability for the deaf.  There are statistically significant differences in the level of mental health of the hearing impaired due to the economic level in favor of (average).
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: الاعاقة السمعية، الصحة النفسية; Déficience auditive, santé mentale; Hearing impairment, mental health